Structures and granular solids : from scientific principles to engineering application : an international conference in celebration of the 60th birthday of Prof. J. Michael Rotter : proceedings of the International Conference on Structures and Granular Solids : From Scienctific Principles to Engineering Applications, the Royal Society of Edinburgh, Scotland, UK, 1-2- July 2008 /: from scientific principles to engineering application : an international conference in celebration of the 60th birthday of Prof. J. Michael Rotter : proceedings of the International Conference on Structures and Granular Solids : From Scienctific Principles to Engineering Applications, the Royal Society of Edinburgh, Scotland, UK, 1-2- July 2008. (2008) - Unknown
No abstract available